Otsenka effektivnosti adaptivnoi reaktsii pri tsiklicheskoi myshechnoi rabote - Radchenko, A. S.; Borilkevich, V. E.; Zorin, A. I. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of the study was to elaborate the methods of the cardio-respiratory system's adaptative effectiveness in "endurance" running. The subjects (long and middle distances runners and orienteers) distributed in two experimental groups (n1 = 62; n2 = 47) had been tested many times with a help of tredmil running with anaerobic threshold's VE, HR, VO2, VE/VO2, ExcCO2 and O2-Ï detecting. As a result of the research it had been shown: the value of VO2max, speed of running and ExcCO2 to VO2max are directly depended on the effectiveness of exercising with submaximal intensity; VO2 and above indicies demonstrate the significant diurnal fluctuation in one and the same persons; the change of the HR working intensity curve's bending moment correlates with the value of ExcCo2 when working in submaximal regime and its dynamics to VO2max.